Do Children With Functional Abdominal Pain Benefit More From a Pain-Specific Cognitive-Behavioral Intervention Than From an Unspecific Attention Control Intervention? Results of a Randomized Controlled Trial. (5th June 2021) - Warschburger, Petra; Calvano, Claudia; Becker, Sebastian; Ebinger, Friedrich; Hudert, Christian; Iven, Enno; Posovszky, Carsten; Winter, Sibylle-Maria; Daubmann, Anne; Ozga, Ann-Kathrin; Wegscheider, Karl
Abstract : INTRODUCTION: We aimed to compare the efficacy of cognitive-behavioral therapy (CBT) among children with functional abdominal pain with an attention control (AC), hypothesizing the superiority of CBT group intervention regarding pain intensity (primary outcome), pain duration and frequency (further primary outcomes), functional disability, and quality of life and coping strategies (key secondary outcomes). METHODS: We conducted a prospective, multicenter, randomized controlled efficacy trial (RCT) with 4 time points (before intervention, after intervention, 3-month follow-up, and 12-month follow-up). One hundred twenty-seven children aged 7–12 years were randomized to either the CBT (n = 63; 55.6% girls) or the AC (n = 64; 57.8% girls). RESULTS: Primary endpoint analysis of the logarithmized area under the pain intensity curve showed no significant difference between groups (mean reduction = 49.04%, 95% confidence interval [CI] −19.98%–78.36%). Treatment success rates were comparable (adjusted odds ratio = 0.53, 95% CI 0.21–1.34, number needed to treat = 16). However, time trend analyses over the course of 1 year revealed a significantly greater reduction in pain intensity (40.9%, 95% CI 2.7%–64.1%) and pain duration (43.6%, 95% CI 6.2%–66.1%) in the CBT compared with the AC, but not in pain frequency per day (1.2, 95% CI −2.7 to 5.2). In the long term, children in the CBT benefitted slightly more than those in the AC with respect to functional disability, quality of life, and coping strategies. DISCUSSION: Both interventions were effective, which underlines the role of time and attention for treatment efficacy. However, in the longer term, CBT yielded more favorable results.